Protocol for preparing layer-engineered van der Waals materials through atomic spalling - Moon, Ji Yun; Kim, Seung Il; Josline, Mukkath Joseph; Kim, Chan Young; Kim, Jin Su; Kim, Ina; Jung, Euna; Lee, Jae Hyun (STAR Protocols, 2023)
Here, we present a protocol for preparing layer-engineered van der Waals (vdW) materials via an atomic spalling process. We describe steps for fixing bulk crystals and introduce the appropriate stressor materials. We then detail a deposition technique for internal stress regulation of stressor film, followed by layer-engineered atomic-scale spalling to exfoliate vdW materials with a controlled number of layers from bulk crystals. Lastly, we outline a procedure for polymer/stressor film removal. For complete details on the use and execution of this protocol, please refer to Moon et al.1
Keywords: Material Sciences; Physics